The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijerph16245034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Biochar Impact on Topramezone Adsorption Behavior on Soil under No-Tillage and Rotary Tillage Treatments: Isotherms and Kinetics

Abstract: The evaluation of biochar application on the adsorption behavior of topramezone on soil under no-tillage (NT) and rotary tillage treatments (RT) has been assessed. Fourier Transform Infra-Red Spectrometry (FTIR), scanning electron microscopy (SEM), and Brunauer–Emmett–Teller) (BET) were used for the biochar characterization. Batch experiments were carried out in a laboratory to assess the adsorption of topramezone on soil through equilibrium and kinetic modeling under biochar addition. The clay content has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Wu et al, reported that this kinetics model described the Pb (II) adsorption using biochar [57]. Furthermore, the same trend was reported in other studies [58,59]. The main advantage of using cyanobacterial biomass as a biosorbent source is that this application can resolve the eutrophication problems generated by cyanobacterial growth in the swamp of Malambo.…”
Section: Model Parameterssupporting
confidence: 64%
“…Wu et al, reported that this kinetics model described the Pb (II) adsorption using biochar [57]. Furthermore, the same trend was reported in other studies [58,59]. The main advantage of using cyanobacterial biomass as a biosorbent source is that this application can resolve the eutrophication problems generated by cyanobacterial growth in the swamp of Malambo.…”
Section: Model Parameterssupporting
confidence: 64%
“…During 180 to 1440 min, the DEA adsorption rate of soil and BC soil slowed down, which illustrates that the adsorption process entered the slow stage. This was mainly because the DEA molecule was rapidly adsorbed by active adsorption sites on the surface of the soil and BC soil during the initial stage of the reaction (Uwamungu et al 2019). As the reaction progressed, active adsorption sites were gradually occupied by DEA, which then entered the micropore structure inside the biochar and soil for relatively slow micropore filling.…”
Section: Effects Of Biochar On Dea Adsorption Kinetics In Different Soil Typesmentioning
confidence: 99%